Carbon nanotube supported direct borohydride fuel cell anode catalysts: the effect of catalyst loading - Aykut Caglar; Hilal Demir Kıvrak; Ömer Şahin; Tulin Avcı Hansu (MANAS: Journal of Engineering)
At present, monometallic CNT supported Pd electrocatalysts (Pd/CNT) are prepared at varying Pd loadings via sodium borohydride (NaBH4) reduction method to investigate their NaBH4 electrooxidation activities. These monometallic Pd/CNT catalysts are characterized by X-ray Diffraction (XRD), N2 adsorption-desorption, Fourier-Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy-Energy Dispersive X-ray analysis (SEM-EDX). Characterization results are revealed that Pd/CNT metallic Pd with a face center cubic structure is detected. The crystallite size corresponding to (1 1 1 ) plane is found as 5.87 nm for 30% Pd/CNT catalyst. The average pore size, pore-volume, and Brunauer, Emmet ve Teller (BET) surface area of Pd/CNT are obtained as 24.5 nm, 0.93 cm³/g, and 129.48 cm2/g, respectively. From the SEM-EDX results, it indicates that the Pd metal is homogeneously distributed in the carbon structures. NaBH4 electrooxidation measurements are performed with cyclic voltammetry (CV), chronoamperometry (CA), and electrochemical impedance spectroscopy (EIS). The effect of Pd loading (0.1-70.0 %) for NaBH4 electrooxidation is investigated via CV. The 30% Pd/CNT catalyst exhibits the highest electrochemical activity with a current density of 16.5 mA cm-2. By altering Pd loading, catalyst surface electronic structure changes significantly, leading to enhanced NaBH4 electrooxidation activity. CA and EIS measurement results are agreement with CV results. As a conclusion, it is clear that Pd/CNT catalysts are promising catalysts for direct borohydride fuel cells.